COVID-19 Impacts on Teaching and Learning: A Collaborative Autoethnography by Two Higher Education Lecturers - Godber, Kathleen Ann; Atkins, Denise Robyn (Frontiers in Education, 2021)
The phenomenon of the Covid-19 lockdown in New Zealand during 2020 enabled two Higher Education (HE) lecturers to reflect on grappling with new technologies, changes in lifestyle and livelihoods, and the impact that social isolation had on Bachelor of Sport and Recreation (BSR) students as they shifted to emergency ‘remote’ teaching and learning. This paper presents personal narratives, authored collaboratively by lecturers Anna and Hana (pseudonyms), engaging with a socio-ecological systems framework. The systems framework presents a layered, multi-faceted approach to reveal the complexity of the impacts of Covid-19 on HE teaching and learning. In-depth analysis of the microsystems, mesosystems, and macrosytems making up their systems framework, serve to highlight specifically how Anna and Hana interpreted their own and their university students' responses to the unprecedented measures imposed on their lifestyle (home), livelihood (employment, and HE experience (online learning). By applying an autoethnographic methodology, this paper acknowledges and celebrates the lecturers' subjectivity, emotionality, and influence on the presented research. As educators, their critical self-reflections are authentic and timely, expressing key concerns and considerations, while searching for optimal solutions to deliver equal and equitable learning opportunities for all students. A unique characteristic of this phenomenon was the inability (due to COVID-19 restrictions) of students who learn through practical contexts, to enact kinaesthetically in a meaningful manner, and the subsequent implications on their learning. This paper presents a snippet of the lecturers’ reflective practice, co-constructed from recollections, memories, and anecdotal evidence, against a backdrop of current Covid-19 research on the effects of the pandemic, on teaching and learning globally. Whilst this paper sheds light on the experiences of two HE lecturers during the Covid-19 lockdown, a collection and analysis of ‘student’ voice, is recommended. This paper concludes that a collaborative autoethnographic approach during exceptional circumstances, such as natural disasters, pandemics, and other disruptive situations, provides an opportunity for professional self-observation and self-reflective practice, that is mutually beneficial, and empowering. These insights provide critical knowledge to sustain achievement while averting negative impacts, for students and lecturers alike.